Preservative Action of Ginger and Garlic Ratio Mixture on Fresh Leaves of Moringa oleifera with its Computational Evidences - Pattanaik, S.; Mohapatra, A.; Rath, D.; Kar, D.M.; PANDA, J.; Rath, A. (Asian Journal of Chemistry, 2022)
In food industries worldwide, food processing methods are tremendously needful to meet the present consumer’s demands. There are continuously increasing efforts to develop food preservatives by avoiding chemicals for which natural sources are the only alternative. Morninga oleifera (Moringaceae) is highly nutrious and medicinaly valued plant which will be detoriate with the microbial and environmental factors. The preservation of food materials is really challenged without using the chemical preservatives. The use of spice property of ginger and garlic has a characteristic pungent, hot, flavour that mellows and sweetens considerably with cooking. They both have the radical scavenging activity otherwise considered ideal antioxidants beneficial in many reported diseases including the antifungal, antibacterial and antiviral and antiparasitic agents. Therefore, the present study has been undertaken to investigate the popularly used ginger and garlic in the management of antimicrobial activity of leaves of Morninga oleifera by in vitro as well as in silico approaches.